Male Rural-to-Urban Migrants and Risky Sexual Behavior: A Cross-Sectional Study in Shanghai, China - Wu, Jun-Qing; Wang, Ke-Wei; Zhao, Rui; Li, Yu-Yan; Zhou, Ying; Li, Yi-Ran; Ji, Hong-Lei; Ji, Ming (International journal of environmental research and public health, 2014)
This study examined the prevalence and the determinants of risky sexual behavior (defined as having multiple sex partners and paying for sex) among male rural-to-urban migrants in China. An anonymous questionnaire was used to collect information on socio-demographics, knowledge, attitudes, and behavior associated with increased risk of risky sexual behavior from 4,069 subjects. In total 1,132 (27.8%) participants reported two or more sex partners and 802 (19.7%) participants paid for sex. A considerable proportion (29.6%–41.5%) did not use a condom during risky sexual behavior. Logistic regression analysis revealed that unmarried status (OR: 0.62, CI: 0.42–0.85 for married), earlier age at first sexual experience (OR: 0.67, 95% CI: 0.31–0.91 for ≥22 years old), poor perception of risk of acquiring HIV/AIDS (OR: 1.51, 95% CI: 1.33–1.96 for unlikely; OR: 2.38, 95% CI: 1.61–3.70 for impossible), frequent exposure to pornography (OR: 0.67, 95% CI: 0.60–0.81 for sometimes; OR: 0.31, 95% CI: 0.11–0.43 for never), attitudes toward legalization of commercial sex (OR: 0.39, 95% CI: 0.21–0.59 for no), peer influence (OR: 0.51, 95% CI: 0.27–0.88 for no), and not knowing someone who had/had died from HIV/AIDS (OR: 0.35, 95% CI: 0.20–0.53 for yes) were all significantly associated with having multiple sex partners. Those who paid for sex showed similar findings.